Living with Xenophobia : Zimbabwean Informal Enterprise in South Africa - Crush, Jonathan, 1953- (Southern African Migration Programme (SAMP), 2017)
This report examines the impact of xenophobic violence on Zimbabweans who are trying to make a living in the South African informal sector and finds that xenophobic violence has several key characteristics that put them at constant risk of losing their livelihoods and their lives. The businesses run by migrants and refugees in the informal sector are a major target of South Africa's extreme xenophobia. Attitudinal surveys clearly show that South Africans differentiate migrants by national origin and that Zimbabweans are amongst the most disliked. This report is based on a survey of informal sector enterprises in Cape Town and Johannesburg; and 50 in-depth interviews with Zimbabwean informal business owners in Cape Town, Johannesburg and Polokwane who had been affected by xenophobic violence. In many areas, community leaders are ineffective in dealing with the violence and, in some cases, they actively foment hostility and instigate attacks. The fact that migrant entrepreneurs provide goods, including food, at competitive prices and offer credit to consumers is clearly insufficient to protect them when violence erupts. However, the deep-rooted crisis in Zimbabwe makes return home a non-viable option and Zimbabweans instead adopt several self-protection strategies, none of which is ultimately an insurance against xenophobic attack. The findings in this report demonstrate that xenophobic violence fails in its two main aims: to drive migrant entrepreneurs out of business and to drive them out of the country.
Keywords: Informal sector (Economics) -- South Africa.; Xenophobia -- South Africa.; Zimbabweans -- South Africa -- Social conditions.; Immigrants -- Violence against -- South Africa.; South Africa -- Emigration and immigration -- Economic aspects.; Entrepreneurship -- Social aspects -- South Africa.; Small business -- Social aspects -- South Africa.; Secteur informel (Économie politique) -- Afrique du Sud.; Xénophobie -- Afrique du Sud.; Zimbabwéens -- Afrique du Sud -- Conditions sociales.; Entrepreneuriat -- Aspect social -- Afrique du Sud.; SOCIAL SCIENCE -- Discrimination & Race Relations.; Informal sector (Economics); Xenophobia; South Africa; Emigration and immigration -- Economic aspects; Entrepreneurship -- Social aspects; Small business -- Social aspects; Zimbabweans